Influence of nitrogen, phosphorus and potassium levels on growth, seed yield and essential oil content in anise (Pimpinella anisum L.) - B S Sreeramu, K N Srinivasappa, Bhuvaneshwari Bhuvaneshwari, A A Farooqi (Journal of Spices and Aromatic Crops, 2002)
A field experiment was conducted to study the influence of three levels, each of nitrogen (0, 40 and 80 kg ha-1), phosphorus and potassium (each at 0, 30 and 60 kg ha-1) on growth, seed yield and essential oil content in anise at Horticultural Research Station, University of Agricultural Sciences, Bangalore. The results of the study revealed significant differences among the treahnents with respect to growth, seed yield and essential oil content. The interaction of nitrogen at 80 kg ha-1, phosphorus and potassium each at 60 kg ha-1 was found to be significant, recording highest values for growth characters like plant height (62.47 cm), number of leaves (33.33) and total leaf area (653.27 cm2) per plant and yield parameters such as number of fruits per umbel (595.17), size of the umbel (38.93 cm2) and also seed yield (698 kg ha-1) compared to control (189 kg ha-1). This treatment also gave the highest essential oil yield of 24.41 kg ha-1.